Statistical and geospatial assessment of trace and toxic elements distribution in ground and surface water of northern parts of the Indo-Gangetic plains: Source identification and health risk assessment - Kumar, Manoj; Kumar, Sunil; Lovish (Chemosphere (Oxford), 2024)
This study focusses on ground and surface water resources in the northern parts of the Indo-Gangetic Plains. The study aims to identify potential contaminants, analyse their distribution, trace their origins, and evaluate associated health risk. Samples from 80 locations; groundwater (n = 69) and surface water (n = 11) were analysed for nineteen trace and toxic elements using ICP-MS. Eight elements in groundwater (Mn, Fe, Ni, Zn, As, Tl, U and Se) and six in surface water (Al, Mn, Fe, Ni, Zn, and Tl) exceeded WHO (2011) and BIS (2012) limits in certain areas. The geospatial analysis reveals hotspots of trace and toxic element concentration, with higher levels detected in the southeast and western regions of the study area. Correlation matrices revealed a robust correlation (∼>0.75–0.99, p < 0.01) among all trace and toxic elements (excluding Li, Be, As, Ag, and U) in surface water samples when compared to groundwater samples. Cluster analysis and principal component analysis (PCA) (explains 70.09 cumulative percent for total 6 of factors) of groundwater chemistry indicates that Zn, Ni and Tl contamination may originate from industrial activities (metallurgical processes and manufacturing). The potential sources of Mn may be both geological and human-induced, while Fe, Se, As and U can originate from specific geological formations or human-related activities like over-extraction and leaching of excess fertilizers into aquifers. For surface water, PCA (explains 92.92 cumulative percent for total 5 of factors) identifies industrial activities as the main source of Mn, Fe, Tl, Ni, and Zn, while Al originates from both geological and anthropogenic sources. The water quality index indicated poor to very poor water quality in the western and central regions, whereas the northern and eastern regions exhibited excellent water quality. Health risk assessment reveals HI values for groundwater water: 3.85 (adults), 7.70 (children); surface water: 1.52 (adults), 3.05 (children), emphasizing the urgent need for remediation measures. [Display omitted] •Robust analytical approach: High recovery rates, low RSDs.•Exceedances: Al, Mn, Fe, Ni, Zn, As, Tl, U and Se at specific locations.•Diverse contamination sources: Industrial, geological, agricultural.•Geospatial hotspots identified: South-east, west regions.•Urgent health concerns: Zinc, uranium exceed safe levels.